PERMASALAHAN DAN PERAWATAN POMPA SENTRIFUGAL DI PT. MEDCO E&P INDONESIA - , MUHERWANTO; , Ir. Susanto Johanes, MT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
With the increasing production at PT. MEDCO E & P INDONESIA especially in S & CS Asset, then the chances for a unit centrifugal pumps will be greater. To improve the quality and efficiency of work in particular pompa Reciprocating Pompa then writing about the trouble and care essential centrifugal pumps. Writing about his own centrifugal pumps due to lack of media or references to trouble and care centrifugal pumps in Indonesian, as well as to support existing methods of treatment, especially in the oil. The role of this thesis is important because as a media reference in carrying out maintenance process. to complete the final task of a centrifugal pumps maintenance is divided into two ways are the daily maintenance and preventive maintenance inspection. This final project, successful maintenance of centrifugal pumps. and damage to the junk clogging centrifugal pumps are the eye of the impeller causing decreased suction capacity, shaft bent or jammed, damaged bearings, high vibration, casing leak after preventive maintenance and daily maintenance centrifugal pumps aback to work optimally.